Printed Media and Artificial Intelligence: Sentiment Analysis of News about the Workers' Party in Ponta Grossa, PR, Brazil, in the 1980s (Terr@ Plural, 2022)
This paper aims to understand how the news in newspapers referring to the Workers’ Party (PT) in Ponta Grossa in the 1980s can be understood through Sentiment Analysis. In this sense, the journalistic publications of a certain spatial and temporal cut are analyzed, with the use of opinion mining techniques applying artificial intelligence to decipher aspects of natural language. We used the Syuzhet package included in Rbase, through the Rstudio interface, where we could verify that the positive emotions and feelings transmitted by the news published during the time under analysis, contributed to the electoral adhesion to the PT, electing members in the legislative and executive branches of the municipal government, a situation that had its share of influence in later decades in other spheres of the State. In this paper we try to make clear the path is taken to reach our results, allowing the methodology to be applied to other printed periodicals and other themes.
Keywords: Print Newspapers; Worker's Party; Syuzhet; Sentiment Analysis